Differential count and time-course analysis of the cellular composition of coelomocyte aggregate of the Japanese sea cucumber Apostichopus japonicus. (November 2016) - Taguchi, M.; Tsutsui, S.; Nakamura, O.
Abstract: Echinoderms have many types of coelomocytes, which have been known to form aggregates immediately after they are removed from the coelom. To assess the roles that each type of coelomocyte plays in aggregate formation, cellular components of coelomocyte aggregates of the Japanese sea cucumber, Apostichopus japonicus, were investigated. The coelomocytes were tentatively classified into 12 types based on May-Grunwald/Giemsa staining. After the coelom was incubated for 30 min or 6 h, the aggregates were disaggregated completely with 200 mM EDTA. Differential counts of the dissociated cells indicated that the largest component of the aggregates was amoebocytes (67.8%) and the second-largest component of the aggregates incubated 30 min was a type of basophilic granulocyte. In the 6h-incubated aggregates, the fraction of amoebocytes decreased to 59.0%, while that of lymphoid cells significantly increased, which suggests that lymphoid cells participate in late-stage aggregation. After 24-h incubation, only a portion of the aggregated cells could be disaggregated with EDTA. After 48 h, most of the cells could not be detached from the aggregates. Microscopy of frozen sections of the aggregates after 6-h incubation revealed that amoebocytes constructed a mesh-like structure to which other types of cells adhered. After 48 h, the borders of the cells and the intracellular granules were not recognizable. In time-lapse microscopy, the aggregates were observed to move on a glass slide, which suggests that aggregates can "crawl" on the intraluminal surface of the coelom toward, for example, injured regions in the body of the sea cucumber. Highlights: The coelomocytes of A. japonicus were classified into 12 types. Cellular aggregates were dissociated with EDTA and differential count was performed. Amoebocytes accounted for 70% in aggregates incubated 30 min but decreased later. Lymphoid cells increased from 6.3% to 21% of the aggregates within 6 h.